Implementasi Pembelajaran Berbasis E-Learning Dalam Memudahkan Pekuliahan Mahasiswa PGMI di IAI Al Khoziny Sidoarjo - Dachlan, Abd. Malik; ,, Taseman (Institut Agama Islam Al-Hikmah Tuban, 2023)
The covid-19 pandemic occurred throughout the world in 2019 changing the structure of society in any aspect and was declared an outbreak by the World Health Organization (WHO) in March 2021. Education is affected so that it requires online-based learning with E-Learning Based learning to Facilitate PGMI Student Lectures at IAI Al Khoziny Sidoarjo, the research method used is qualitative descriptive narrative using a questionnaire in collecting data from students via google form. The results of the study answered; 1). Applications used in E-learning, 2). The power of the internet used in E-learning, 3). The type of connection used, 4) Media used in E-learning, 5) Management in giving assignments, 6) Understanding in E-learning. As for each point, it has benefits in the Implementation of E-Learning Based Learning for PGMI Students to take part in lectures at IAI Al Khoziny Sidoarjo, with the existence of e-learning online learning can be carried out well through the support of all internet facilities provided by the campus, therefore the implementation is very useful and has a positive impact on e-learing based learning. Keywords; Keywords; Implementation, E-Learning Based Learning, Facilitating Lectures, PGMI Students at IAI Al Khoziny Sidoarjo